Just need somebody to double check a few problems for me.

lim 9-x^2/x-3

x->3

lim -(x-3)(x-3)/x-3 =

x->3

-(x+3) = -(3+3) = -6

Next problem

lim x^2 +x-6/x-2

x->2

Lim (x+3)(x-2)/x-2 =

x->2

lim x+3=

x->2

2+3=5

Printable View

- March 29th 2006, 10:58 AMbeckyLimits
Just need somebody to double check a few problems for me.

lim 9-x^2/x-3

x->3

lim -(x-3)(x-3)/x-3 =

x->3

-(x+3) = -(3+3) = -6

Next problem

lim x^2 +x-6/x-2

x->2

Lim (x+3)(x-2)/x-2 =

x->2

lim x+3=

x->2

2+3=5 - March 29th 2006, 01:17 PMtopsquarkQuote:

Originally Posted by**becky**

A tip. Your first problem is:

If you click on the expression above it will tell you how to code it in LaTeX. Otherwise you might want to consider using parenthesis so that your expression is unambiguous.

-Dan